Communication difficulties reported by patients diagnosed with idiopathic pulmonary fibrosis and their carers: a European focus group study. Issue 2 (4th June 2019) - Masefield, Sarah; Cassidy, Nicola; Ross, Derek; Powell, Pippa; Wells, Athol
This paper explores commonalities in the experience and unmet needs of idiopathic pulmonary fibrosis (IPF) patients and carers in Europe throughout the care pathway, focusing specifically on the unmet communication needs of patients and carers. Four patient organisations/groups in Europe held focus groups (Italy (seven patients and four carers); Belgium (six patients); Ireland (23 patients and 10 carers); and England, UK (five patients and three carers)). A focus group schedule was provided and translated into the language of each focus group by the European Lung Foundation (ELF). Content analysis was conducted by the ELF and verified by the authors of the paper. Three main themes emerged: professional−patient, professional−professional and patient−patient communication. Within these themes, eight priority areas were highlighted by two or more of the focus groups. In addition, 17 suggested action points were identified. Patients and carers in Europe have unmet communication needs, which could be met by specialist physicians and specialist centres providing more effective information and signposting to support services, including support groups and patient organisations. People with IPF and their carers reported communication challenges with healthcare professionals, between healthcare professionals and from patient to patient, during four focus groups held in different countries in Europe http://bit.ly/2LaJXQF